PI3K/Akt and MAPK pathways evoke activation of FoxO transcription factor to undergo neuronal apoptosis in brain of the silkworm Bombyx mori (Lepidoptera: Bombycidae) - Kim, J. H.; Choi, J-S.; Lee, B. H. (Cellular and Molecular Biology, 2012)
The Forkhead box O (FoxO) transcription factors, including FoxO1, FoxO3a, FoxO4, and FoxO6, are implicated in the regulation of cell apoptosis and survival. Here, we examined the role of FoxO transcription factors and the involvement of the PI3K/Akt and mitogen-activated protein kinase (MAPK) pathways in neuronal apoptosis in the brain of the silkworm Bombyx mori following starvation. Starvation inhibited cell proliferation and induced apoptosis through caspase-3 activation. The level of phosphorylated kinase Akt increased when the animals ceased feeding. Starvation conditions reduced extracellular-signal-regulated kinase phosphorylation but increased both c-Jun N-terminal kinase and p38 (MAPK) phosphorylation. FoxO1 and FoxO3a were simultaneously localized in the nuclei. These results provide new insights into the process of apoptosis of brain neurons through the involvement of FoxO transcription factors following starvation of insect species.